Gambaran Resiko Ergonomi Menggunakan Metode (NBM) pada Karyawan Kantor PT.PLN (Persero) Surabaya Selatan - Achmad Isya Nyoman; Abdul Hakim Zakkiy Fasya; British Shimahero; Reza Maulana Nur Hidayat (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
In today's use of computers has a very diverse function in human activities, it is found that most office workers complete more than 75% of the duration of their work sitting in front of the computer.Â Computer users or office workers often experience health problems related to Musculoskeletal Disorder (MSDs) is a health problem that can reduce the function of muscles, tendons, nerves, blood vessels, bones, and ligaments caused by awkward posture, ergonomic risks that often occur in office workers. The research method used is an analytical method. February 2023. PT PLN (Persero) UP3 South Surabaya has six ULP, namely Rungkut ULP, Darmo Permai ULP, Dukuh Kupang ULP, Ngagel ULP, Gedangan ULP. There were 50% of respondents aged >35 years, male gender 55%, working period >10 years 64%, and 68% work duration for 6-8 working hours. Â The results of the NBM analysis provide information on changes in the distribution of musculoskeletaldisorders (MSDs) complaint rates of office workers are not sick (TS) = 4 5%, somewhat sick (AS) = 43.1%, sick (S) = 10.5%, very sick (SS) = 2.4%. The most dominant type of complaint for S complaint levels both before and after work is